Muscle and Anaerobic Performance Relationships With Firefighter Occupational Tasks: A Systematic Review and Meta-Analysis. - Martin, Joel R.; Abel, Mark G.; Newman, Kayleigh; Fyock-Martin, Marcie; Clark, Nicholas C. (Journal of Strength & Conditioning Research, 2026)
Supplemental Digital Content is Available in the Text. Martin, JR, Abel, MG, Newman, K, Fyock-Martin, M, and Clark, NC. Muscle and anaerobic performance relationships with firefighter occupational tasks: A systematic review and meta-analysis. J Strength Cond Res 40(4): 476–510, 2026—Firefighting requires performing a variety of physically demanding occupational tasks. Subsequently, understanding physical fitness correlates for occupational performance tests (OPTs) is crucial for optimizing firefighter training and readiness. The purpose of this review was to examine the relationship between muscle and anaerobic performance measures with the completion of firefighting OPTs. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and included studies with firefighters and reporting relationships between measures of muscle and anaerobic performance with OPT outcomes. Random effects models were used to calculate pooled correlation coefficients. Thirty-two studies were included and assessed muscle and/or anaerobic performance using varied assessment protocols and OPTs that simulated firefighting tasks such as stair climb, equipment carry, ladder raise, victim drag, and forcible entry. The pooled correlations for time to complete OPTs consisting of circuits of firefighting tasks ranked from strongest to weakest were anaerobic capacity, anaerobic power, lower body strength, upper body strength, upper body endurance, lower body endurance, and core endurance. For single firefighting task OPTs, pooled correlations indicated muscle and anaerobic performance had varied associations with OPT completion time, dependent on task-specific biomechanical and physiologic demands. The cumulative findings highlight the importance of muscle and anaerobic fitness for performing firefighting task OPTs. A physical fitness assessment for firefighters could include the isometric mid-thigh pull, handgrip, maximum push-ups, and either a Wingate test or 400-meter sprint. Results from these assessments can guide training programs to meet entry requirements, maintain readiness, and support postinjury return to duty.